1986
DOI: 10.1093/ajcp/85.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Interference by IgG Paraproteins in the Jaffe Method for Creatinine Determination

Abstract: A large (60-100%) negative interference in serum creatinine value of some (3 of 18 myeloma patients, all with monoclonal gammopathy of IgG type, was observed on several instruments that determine creatinine by the Jaffe reaction. No interference was observed in an enzymatic method. Serum electrophoresis showed a monoclonal band in all three samples. The interferent could be removed by acid precipitation or dithiothreitol preincubation, and partially isolated in the high molecular weight dialyzate from the seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…(1 ) and Pantanowitz et al (8 ) described this artifact as rare, but we have identified 6 patients at 2 hospitals with documented paraproteins who had falsely increased serum total bilirubin. Notably, patients with artifactually high total serum bilirubin had direct bilirubin values within the reference interval.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…(1 ) and Pantanowitz et al (8 ) described this artifact as rare, but we have identified 6 patients at 2 hospitals with documented paraproteins who had falsely increased serum total bilirubin. Notably, patients with artifactually high total serum bilirubin had direct bilirubin values within the reference interval.…”
mentioning
confidence: 79%
“…The total bilirubin assay on the Hitachi 917 automatic chemistry analyzer (Roche Diagnostics) has been reported to yield falsely increased bilirubin values as a result of paraprotein interference (1,8 ).…”
mentioning
confidence: 99%
“…As described in previous literature paraproteins are known to cause interference in the estimation of several biochemical parameters including total bilirubin, albumin, creatinine, phosphate, calcium and iron in human serum [2][3][4][5][6][7][8]. The falsely elevated serum bilirubin level is supposed to result from a white precipitate arising out of reaction of paraprotein with the solubilizing agent in total bilirubin reagent [2].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous examples of such interference have appeared as case reports and reviews, and monoclonal IgM is often responsible. [8][9][10][11][12][13][14][15][16][17] Due to the intermittent nature of the interference and the frequent reformulation of reagents by manufacturers, this type of laboratory error is difficult to anticipate, but it can be recognized within the laboratory by alert staff and brought to the attention of clinical colleagues to avoid misinterpretation. Some of the laboratory tests prone to interference by hyperparaproteinemia include: albumin, creatinine (Jaffe method), C-reactive protein, hemoglobin, MCH, MCHC, inorganic phosphate, thyroxine, urea nitrogen, uric acid, and sodium.…”
Section: T2mentioning
confidence: 99%